EHL Optimal Design of Modified Helical Cylindrical Gear - 唐群国; 陈卓如; 陈谌闻 (Jixie chuandong)
The modification of tooth profile can effectively decrease the impact,vibration, and noise, increase the load carrying capacity in gearing. Many kinds of methods of modificationhave been put forward in order to alleviate the stiffness fluctuation in gear engagement cycle and improve load distribution. From the viewpoint of improving the EHL conditions between gear teeth, with diagonal modification as an example, modification parameters are cptimized so that the optimum EHL effect can be achieved.